A catalogue of the Talfourd P. Linn Collection of Cervantes materials, on deposit in the Ohio State University Libraries. Compiled by Dorothy Petersen Ackerman. Edited by Paul J. Kann and Rolland E. Stevens. Ohio State University Press, [Columbus, Ohio], 1963; xiv + 107 pp. - Vergara, M. A. (Nueva Revista de Filología Hispánica (NRFH), 1970)
Se reseñó el libro: A catalogue of the Talfourd P. Linn Collection of Cervantes materials, on deposit in the Ohio State University Libraries.